AbYsis: Integrated Antibody Sequence and Structure—Management, Analysis, and Prediction. Issue 3 (3rd February 2017) - Swindells, Mark B.; Porter, Craig T.; Couch, Matthew; Hurst, Jacob; Abhinandan, K.R.; Nielsen, Jens H.; Macindoe, Gary; Hetherington, James; Martin, Andrew C.R.
Abstract: abYsis is a web-based antibody research system that includes an integrated database of antibody sequence and structure data. The system can be interrogated in numerous ways—from simple text and sequence searches to sophisticated queries that apply 3D structural constraints. The publicly available version includes pre-analyzed sequence data from the European Molecular Biology Laboratory European Nucleotide Archive (EMBL-ENA) and Kabat as well as structure data from the Protein Data Bank. A researcher's own sequences can also be analyzed through the web interface. A defining characteristic of abYsis is that the sequences are automatically numbered with a series of popular schemes such as Kabat and Chothia and then annotated with key information such as complementarity-determining regions and potential post-translational modifications. A unique aspect of abYsis is a set of residue frequency tables for each position in an antibody, allowing "unusual residues" (those rarely seen at a particular position) to be highlighted and decisions to be made on which mutations may be acceptable. This is especially useful when comparing antibodies from different species. abYsis is useful for any researcher specializing in antibody engineering, especially those developing antibodies as drugs. abYsis is available atwww.abysis.org . Graphical Abstract: Highlights: abYsis is a web-based antibody research system that integrates sequence data from EMBL-ENA and Kabat with sequence and structure data from the Protein Data Bank. It allows searches based on text, sequence data, and structural constraints. It automatically numbers sequences and provides detailed annotations to aid interpretation. Users can upload and analyze their own sequences in the same way via the web interface. It provides a comprehensive set of position and species-specific residue distributions. Additional advanced tools are provided to assess antibody characteristics such as humanness.